Poverty Reduction and Economic Development in Nigeria - Adeleke, Kareem O.; Kolapo, Funso T.; Edewusi, Damilola G. (Archives of Business Research, 2022)
Extant literature shows that the incidence of poverty is one of the biggest threats to human development, however, not many studies have acknowledged the important role of financial development and access to internet services in reducing the incidence of poverty to enhance economic development. Therefore, this study examined the relationship between poverty reduction and economic development in Nigeria using data for the period of 2003Q1 to 2019Q4. The data for this study is collected from the United Nations Human Development Reports and the World Bank’s World Development Indicators Database. Using the Autoregressive Distributed Lag Model-Error Correction Modelling (ARDL-ECM) estimator, the results of the ARDL long-run estimates showed that poverty reduction, financial development, economic growth, trade openness, and the internet had positive and significant effects on human development. Furthermore, urbanisation had a negative but non-significant effect on human development, indicating a negative coefficient and exact p-value of 0.064735 and 0.8221. Meanwhile, the results of the ARDL short-run estimates except for urbanisation are consistent with the long-run results. Besides, the Error Correction Model (ECM), which indicates the speed of adjustment back to long-run equilibrium level after a short-run disturbance, showed a coefficient which is negative (-0.145327) and significant at 1% level of significance, implying that about 15% of any disequilibrium in the short-run is adjusted back to the long-run equilibrium in each quarter. Based on the long-run estimates, the study concludes that poverty reduction is important for economic development in Nigeria. It is, therefore, recommended that the poverty reduction strategies of the Nigerian government should not be pursued in isolation but rather in connection with access to financial and internet services, among other things.